Effects of grape seed proanthocyanidin extract on side effects of high-dose methylprednisolone administration in male rats - Sur, Aslihan; Mutlu, Seda Iflazoglu; Seven, Pinar Tatli; Seven, Ismail; Aslan, Abdullah; Kizil, Meltem; Esen, Selim (Korean Soc Toxicology, 2023)
In this study, we investigated the effects of grape seed proanthocyanidin extract (GSPE) against the side effects of high-dose administration of methylprednisolone (MP) in male rats. A total of 32 adult Wistar male albino rats were divided into four groups: (1) control (CON), received standard food only; (2) MP, received standard food + intraperitoneal injection of 60 mg/kg MP on day 7; (3) GSPE, received standard food + 200 mg/kg/day GSPE; and (4) MP + GSPE, received standard food + 200 mg/kg/day of GSPE + intraperitoneal injection of 60 mg/kg MP on day 7. All animals in the GSPE and GSPE + MP groups were treated once a day by oral gavage for 14 consecutive days. The feed intake of rats in the MP and MP + GSPE groups decreased significantly by 24.14% and 13.52%, respectively (p < 0.05). Administration of MP resulted in significant increases in serum concentrations of blood urea nitrogen (p < 0.001), glucose (p < 0.01), alkaline phosphatase, and adrenocorticotropic hormone (p < 0.05). High-dose MP administration significantly reduced catalase (p < 0.001) and glutathione peroxidase (p < 0.05) concentrations in the liver and kidney tissues of rats, while glutathione concentrations were only reduced in liver tissue (p < 0.05). The expression levels of Bcl-2 and TNF-& alpha; in liver, kidney, and testicular tissue were significantly increased, while the expression levels of caspase-3 were reduced (p < 0.001). Furthermore, sperm concentration was significantly affected by GSPE in rats induced by high-dose MP, and sperm loss was significantly reduced in MP + GSPE (p < 0.05). These findings suggest that GSPE could be useful as a supplement to alleviate MP-induced toxicity in rats.
Keywords: Grape seed proanthocyanidin extract; Methylprednisolone; Apoptosis; Biomarker; Sperm characteristic